Use of Phaseolus trilobatus as Protein Source in the Diet of Labeo rohita Fingerlings - Devi, Chamundeswari; Vijayaraghavan, Shantha (Fishery Technology, 2025)
In the present study groundnut cake was partially replaced with whole seeds of Phaseolus trilobatus at 20%, 40% or 60% levels and the pelleted feeds were fed to the fingerlings of Labeo rohita. The growth performance of the test groups was compared with the control group fed on groundnut cake based pelleted feed over a period of six months. Though all the test groups exhibited significant increase in growth parameters compared to control group, the best growth parameters compared to control group, was observed at 20% inclusion level.